Development of Critical Thinking in Gifted Human by Supply Chain Strategies - Irina Sergeevna, Antonova; Oleg Vladimirovich, Kabanov; Julia Evgenievna, Starostina; Marina Valentinovna, Karageziyan; Tatiana Ivanovna, Yatsunova; Munir Idelovich, Karabaev (International Journal of Supply Chain Management, 2020)
Abstract this article discusses the development of supply chain for the gifted humans in education system. The article describes the experience of identifying potentially gifted students at the initial stage of their education, as well as the organization of work with gifted children in primary school. The article notes that special attention should be paid to the self-realization of a gifted student during the lesson and during extracurricular hours. Finally it confirmed by the reviewing the literature review the effectiveness of supply chin strategy in critical thinking.